Caring for transgender populations: A primer for the dermatopathologist. (5th January 2023) - Sood, Aditya; Stoff, Benjamin K.; Yeung, Howa
Abstract: With increasing access to electronic health records, patients may encounter dermatopathology reports more readily. Dermatopathologists should consider their impact and interactions with transgender patients, who may face specific health and healthcare inequities. Rendering accurate diagnosis for skin diseases requires accurate information about patient's sex assigned at birth and gender identity. Understanding how sex and gender identity data flow between electronic health records, laboratory information systems, insurance billing systems, and patients will be important to avoid patient misgendering, to render accurate diagnoses, to maintain consistency in dermatopathology reports, and to avoid insurance billing denials. Dermatopathologists have important roles to build patient trust in the healthcare system and to help dermatologists diagnose, treat, and characterize skin diseases in transgender populations.